THE CORRELATION STUDY BETWEEN THE REMOVABLE PARTIAL DENTURES USAGE AND THE NUTRITIONAL STATUS OF ELDERLY PATIENTS AT THE USK DENTAL HOSPITAL BANDA ACEH - INDONESIA - Sofya, Pocut Aya; Rahmayani, Liana; Andriany, Poppy; Balqis, Putri (International Journal of Research -GRANTHAALAYAH, 2023)
Introduction, aging is a process in which tissue begins to slowly lose its ability to repair itself and maintain its function. The aging process of the elderly is influenced by several factors, one of which is nutritional improvement. The large number of missing teeth that usually occurs in the elderly results in reduced chewing ability and affects a person's nutritional status. Lost teeth can be replaced by wearing dentures which can help patients restore the efficiency of their chewing abilities. This study aims to determine the relationship between the use of removable partial dentures and the nutritional status of the elderly at the Dental and Oral Hospital of Syiah Kuala University, Banda Aceh. Methods, uses analytical with purposive sampling technique with subjects totaling 33 people. The results showed correlation between the use removable partial dentures and the nutritional status of elderly was 66.7%. Conclusion, there is no significant P 0,243 (P> 0.05) correlation between the use of removable partial dentures and the nutritional status of the elderly at the USK Dental Hospital, Banda Aceh.